Traffic Scheduling Strategy of Power Communication Network Based on SDN - Xiang Min; Zhang Jin Jin; Rao Hua Yang; Ma Rui Heng; Chen Meng Xin (Universitas Sriwijaya, 2020)
Due to the complicated structure, power communication network is difficult to guarantee the quality of service (QoS) of power services. A two-level scheduling algorithm based on software defined network (SDN) is proposed in this paper. Firstly, the priority-based scheduling method is used to meet the latency-sensitive of power service. Then, in order to alleviate congestion, queue bandwidth is adjusted according to network state information, which can be collected by the centralized control of SDN. Finally, the Mininet and Ryu controller are made use of building simulation environment. The test results show that the algorithm proposed in this paper reduce delay and packet loss rate significantly, which achieves QoS.